PERGERAKAN PELAJAR MINANGKABAU: CATATAN MADJALLAH RAYA 1933-1936 - Erman (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2020)
The research aimed to reveal the history of the Raya Magazine and writing on political movements promoted by Islamic College students in Minangkabau. The research findings succeeded in revealing that Raya Magazine was present in the midst of strengthening colonial political pressure and the weakening of the national movement in the 1930s. The political movement was one of the themes of the national movement which was of special note and attention to the Islamic College Students Association. This theme was encountered in several articles during publication, mainly related to the weakening of non-cooperative parties in carrying out movements. The social situation that helped shape the theme of the political movement was the impact caused by the application of vergaderverbood in 1933 and arrested a number of non-cooperative parties leaders, especially Partindo, PNI Baru, and Permi.